Conductive paste, electrode, electronic component, and electronic device
By using a conductive paste containing a zinc-containing surface treatment layer in the electrodes of metals such as silver, the electrode wire breakage caused by vulcanization is solved, and electrode formation with high vulcanization resistance and low cost is achieved.
Patent Information
- Application Number
- CN202380059430.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-26
- Filing Date
- 2023-08-25
- Publication Date
- 2025-03-18
AI Technical Summary
In the prior art, when sulfur oxides and hydrogen sulfide are present in the atmosphere, the silver inside the electrode becomes silver sulfide, which causes the electrode to be broken.
A conductive paste containing surface-treated metal particles is used, which contains 50% by weight or more silver, and a surface treatment layer of zinc compound is formed on the surface of the metal particles to inhibit the vulcanization reaction.
By using the electrode formed by the conductive paste, the vulcanization resistance can be significantly improved, and the vulcanization reaction can be reduced, thereby reducing the incidence of electrode wire breakage and reducing costs.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The present invention relates to a conductive paste used for forming an electrode of an electronic component, for example, and also to an electrode formed using the conductive paste and an electronic component such as a chip resistor having the electrode. Background Art
[0002] In forming the electrodes of a chip resistor, which is a type of electronic component, a conductive paste containing silver powder (silver particles) is used. Figure 1 An example of a cross-sectional structure of a chip resistor 100 is shown in FIG. 1 . The chip resistor 100 has a rectangular alumina substrate 102, and a resistor 104 and a lead electrode 106 for leading electricity from the resistor 104 are formed on the upper surface of the alumina substrate 102. In addition, a lower surface electrode 108 for mounting the chip resistor 100 on the substrate is formed on the lower surface of the alumina substrate 102. In addition, a connecting electrode 110 for connecting the lead electrode 106 to the lower surface electrode 108 is formed on the end surface of the alumina substrate 102. The lead electrode 106 and the lower surface electrode 108 are formed by applying a conductive paste on the upper surface and the lower surface of the alumina substrate 102 by printing and then firing. A nickel plating film 112 and a tin plating film 114 are usually formed on the lead electrode 106, the lower surface electrode 108, and the connecting electrode 110.
[0003] As a conductive paste used for forming an electrode, Patent Document 1 discloses a paste for a chip resistor upper surface electrode in which conductive powder, glass powder, and an inorganic binder are dispersed in an organic vehicle.
[0004] Patent Document 2 discloses a conductive paste comprising (A) surface-treated metal particles containing Ag and Sn, (C) glass powder, and (B) a binder resin, wherein the weight ratio of Sn in the (A) conductive particles is less than 10 weight %.
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent Document 1: Japanese Patent Application Laid-Open No. 7-335402
[0008] Patent Document 2: International Publication No. 2021 / 145269 Summary of the invention
[0009] Problems to be solved by the invention
[0010] In gasoline vehicles and thermal power plants, sulfur oxides are discharged into the atmosphere in large quantities by burning fossil fuels. In addition, in sewage treatment plants and garbage disposal sites, sulfur is reduced by anaerobic bacteria to produce hydrogen sulfide. Therefore, sulfur-containing components such as sulfur oxides and hydrogen sulfide exist in the atmosphere.
[0011] If the sulfur-containing components in the atmosphere reach the surface of metals such as silver, the sulfur components will adhere to the surface of metals such as silver, react with metals such as silver, and become metal sulfides such as silver sulfide. For example, the same reaction occurs in electrodes such as electrodes of chip resistors that use silver as the main material, so there are cases where silver and other metals inside the electrode become metal sulfides such as silver sulfide. If metal sulfides such as silver sulfide are generated inside the electrode, the electrode may be disconnected. Therefore, in devices such as chip resistors that have electrodes made of metals such as silver, malfunctions sometimes occur. Such a phenomenon is called disconnection due to sulfidation. In addition to silver, disconnection due to sulfidation may also occur in electrodes of copper, indium, aluminum, and alloys containing at least one of them.
[0012] In order to improve the performance of the electrode, improving the conductivity is a means. However, if the metal particles are filled with a high amount to improve the conductivity, the degree of sulfidation reaction will also increase accordingly. Therefore, it is required to be able to suppress the disconnection caused by sulfidation even if the conductive paste has a low resistance. In order to suppress the disconnection caused by sulfidation, the electrodes made of metals such as silver as the main material used in devices such as chip resistors need to have high resistance to sulfidation.
[0013] As conductive particles of a conductive paste for forming an electrode with high sulfidation resistance, it has been proposed to use palladium alone or to add a predetermined amount (e.g., about 20% by weight) of palladium. However, since palladium is expensive, the cost of the conductive paste increases by using palladium alone or adding palladium, which leads to a problem of increasing the cost of the electrode.
[0014] Therefore, an object of the present invention is to provide a conductive paste capable of forming an electrode having high sulfidation resistance at a low cost.
[0015] Means for solving problems
[0016] In order to solve the above-mentioned problems, the present invention has the following configurations.
[0017] (Composition 1)
[0018] Configuration 1 is a conductive paste comprising (A) conductive particles and (B) a binder resin, wherein the (A) conductive particles comprise surface-treated metal particles, the surface-treated metal particles comprise metal particles and a surface-treated layer disposed on at least a portion of a surface of the metal particles, and the surface-treated layer comprises a zinc compound.
[0019] (Composition 2)
[0020] Configuration 2 is the conductive paste of Configuration 1, wherein the content of zinc contained in the surface-treated metal particles is 10 to 1000 ppm.
[0021] (Composition 3)
[0022] Configuration 3 is the conductive paste according to Configuration 1 or 2, wherein the surface treatment layer further contains an organic substance.
[0023] (Composition 4)
[0024] Configuration 4 is the conductive paste according to any one of Configurations 1 to 3, wherein the metal particles contain 50 wt % or more of silver.
[0025] (Composition 5)
[0026] Configuration 5 is the conductive paste according to any one of Configurations 1 to 4, wherein the average particle size (D50) of the (A) conductive particles is 0.5 to 10 μm.
[0027] (Composition 6)
[0028] Configuration 6 is the conductive paste according to any one of Configurations 1 to 5, wherein the content of the (B) binder resin is 0.1 to 30 parts by weight based on 100 parts by weight of the (A) conductive particles.
[0029] (Composition 7)
[0030] Configuration 7 is the conductive paste according to any one of Configurations 1 to 6, wherein the conductive paste further includes (C) glass frit.
[0031] (Composition 8)
[0032] Configuration 8 is the conductive paste according to Configuration 7, wherein the (C) glass frit contains ZnO.
[0033] (Composition 9)
[0034] Configuration 9 is the conductive paste of Configuration 7 or 8, wherein the content of the (C) glass frit in the conductive paste is 0.05 to 10 parts by weight based on 100 parts by weight of the (A) conductive particles.
[0035] (Composition 10)
[0036] Configuration 10 is an electrode obtained by firing or heat-treating the conductive paste of any one of Configurations 1 to 9.
[0037] (Composition 11)
[0038] Configuration 11 is the electrode of Configuration 10, wherein the electrode contains 0.1 to 10 wt % of zinc.
[0039] (Composition 12)
[0040] Configuration 12 is an electronic component or an electronic device including the electrode of configuration 10 or 11 .
[0041] Effects of the Invention
[0042] According to the present invention, a conductive paste capable of forming an electrode having high sulfidation resistance at a low cost can be provided. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] Figure 1 This is a schematic diagram showing an example of the cross-sectional structure of a chip resistor.
[0044] Figure 2 It is a schematic diagram showing the shape of the test piece used for the sulfurization resistance test of the Example and the Comparative Example.
[0045] Figure 3 These are optical microscope photographs showing the shapes of test pieces used in the migration resistance test of Examples and Comparative Examples.
[0046] Figure 4 Yes Figure 3 This is an optical micrograph of a test piece for the migration resistance test, in which the center thereof is enlarged.
[0047] Figure 5 This is a scanning electron microscope (SEM) photograph (magnification 5000 times) of the surface of a fired body of the conductive paste after a test piece produced under the same conditions as in Example 3 was stored in a sulfur-containing gas atmosphere for 150 hours to be vulcanized.
[0048] Figure 6 This is a SEM photograph (magnification 5000 times) of a cross section of a fired body of a conductive paste after a test piece produced under the same conditions as in Example 3 was stored in a sulfur-containing gas atmosphere for 150 hours to be vulcanized.
[0049] Figure 7 is corresponding to Figure 6 The energy dispersive X-ray spectroscopy (EDS) analysis result (magnification 5000 times) of the cross-sectional SEM photograph of Example 3 shown is a graph showing the distribution of the silver (Ag) content in grayscale.
[0050] Figure 8 is corresponding to Figure 6The EDS analysis result of the cross-sectional SEM photograph of Example 3 shown (magnification 5000 times) is a graph showing the distribution of the sulfur (S) content in grayscale.
[0051] Fig. 9 This is a SEM photograph (magnification 5000 times) of the surface of a fired body of the conductive paste after a test piece produced under the same conditions as in Comparative Example 1 was stored in a sulfur-containing gas atmosphere for 150 hours to be vulcanized.
[0052] Fig.10 This is a SEM photograph (magnification 5000 times) of a cross section of a fired body of a conductive paste after a test piece produced under the same conditions as in Comparative Example 1 was stored in a sulfur-containing gas atmosphere for 150 hours to be vulcanized.
[0053] Fig.11 is corresponding to Fig.10 The EDS analysis result (magnification 5000 times) of the cross-sectional SEM photograph of Comparative Example 1 shown is a graph showing the distribution of the silver (Ag) content.
[0054] Fig.12 is corresponding to Fig.10 The EDS analysis result (magnification 5000 times) of the cross-sectional SEM photograph of Comparative Example 1 shown is a graph showing the distribution of the sulfur (S) content.
[0055] Fig.13 This is a SEM photograph (magnification 5000 times) of a region where EDS analysis was performed on the amount of zinc on the electrode surface after sulfurization in a test piece prepared under the same conditions as in Example 3.
[0056] Fig.14 The EDS analysis is used to determine the corresponding Fig.13 The results obtained by analyzing the amount of zinc oxide (ZnO) in the SEM photograph of Example 3 are shown in grayscale.
[0057] Fig.15 The EDS analysis is used to determine the corresponding Fig.13 The results obtained by analyzing the amount of zinc aluminate (ZnAlO) in the SEM photograph of Example 3 are shown in grayscale. DETAILED DESCRIPTION
[0058] Hereinafter, embodiments of the present invention will be described in detail. It should be noted that the following embodiments are only modes for embodying the present invention, and the present invention is not limited to the scope thereof.
[0059] The conductive paste of the present embodiment includes (A) conductive particles and (B) a binder resin. The (A) conductive particles include surface-treated metal particles. The conductive paste of the present embodiment can be preferably used to form an electrode of an electronic component such as a chip resistor having an electrode made of a given (A) conductive particle. The (A) conductive particles may include 50% by weight or more of surface-treated metal particles that have been surface-treated with a zinc compound.
[0060] Hereinafter, components contained in the conductive paste of this embodiment will be described.
[0061] <(A) Conductive particles>
[0062] The conductive paste of the present embodiment includes (A) conductive particles. The conductive particles (A) include surface-treated metal particles. The surface-treated metal particles include metal particles and a surface-treated layer disposed on at least a portion of the surface of the metal particles. The surface-treated layer is a thin film containing a zinc compound. The metal particles are surface-treated with a zinc compound to form a surface-treated layer. By making the conductive particles (A) include given surface-treated metal particles, sulfidation of the metal contained in the conductive particles can be suppressed. Therefore, by using the conductive paste of the present embodiment, an electrode with high sulfidation resistance can be formed.
[0063] It should be noted that the inventors of the present invention have found that by making the conductive particles (A) of the conductive paste of the present embodiment contain given surface-treated metal particles, the migration resistance of the obtained electrode is also improved as an additional effect. The so-called migration resistance means the property of being able to suppress migration. The so-called migration is a phenomenon in which, when a voltage is applied to a pair of electrodes (positive and negative electrodes), if there is water and / or water vapor near the electrodes, the metal contained in the electrodes and the wiring parts is ionized and moves from the positive electrode to the negative electrode, resulting in metal dendrites, and the insulation between the wiring parts is reduced. In addition, migration sometimes occurs in an atmosphere without the influence of moisture, such as above 100°C or in a vacuum. In this case, even if a pair of electrodes reaches a state close to a short circuit, there is no generation of dendrites between the wiring parts that is necessarily observed when migration occurs in the presence of moisture, and no polarity is observed (that is, it will occur regardless of the polarity of the positive and negative electrodes). The so-called migration resistance means the property of being able to suppress such migration that has been widely known. Due to the migration of the metal, a pair of electrodes may be short-circuited. By improving the migration resistance, the short circuit of the electrode can be suppressed. In addition, it was found that the migration resistance of the electrode obtained by the conductive paste of the present embodiment is improved not only in the case of the conductive paste of the type fired at a relatively high temperature (e.g., 500 to 900°C), but also in the case of the thermosetting conductive paste that is heat-cured by heat treatment at a relatively low temperature (e.g., 100 to 200°C). However, it is believed that the advantage of improved migration resistance is not necessarily a necessary effect of the conductive paste of the present embodiment, but is an advantage.
[0064] (A) The conductive particles may contain metals other than surface-treated metal particles. However, in order to reliably obtain an electrode with low resistance and high resistance to sulfidation, the conductive particles (A) preferably contain 50% by weight or more of surface-treated metal particles, more preferably 80% by weight or more of surface-treated metal particles, further preferably 90% by weight or more of surface-treated metal particles, and particularly preferably consist only of surface-treated metal particles. It should be noted that in this specification, the so-called "(A) conductive particles consist only of surface-treated metal particles" means that the conductive particles (A) are not intentionally combined with metals other than surface-treated metal particles, and the case of containing conductive particles other than surface-treated metal particles that are inevitably mixed is not excluded.
[0065] (A) The conductive particles may include metal particles of materials such as Zn, In, Al and / or Si as metal particles other than the surface-treated metal particles, within a range that does not impair the effects of the present embodiment. The metal particles contained in the surface-treated metal particles and the metal particles other than the surface-treated metal particles may be alloy metal particles. In addition, the metal particles contained in the surface-treated metal particles and the metal particles other than the surface-treated metal particles may include metal particles of multiple metals or alloys of different types.
[0066] The surface-treated metal particles include metal particles and a surface-treated layer disposed on at least a portion of the surface of the metal particles. The surface-treated layer is a thin film formed on at least a portion of the surface of the metal particles. The metal particles are surface-treated with a zinc compound, thereby forming a surface-treated layer on at least a portion of the surface of the metal particles. Thus, the surface-treated metal particles can be metal particles surface-treated with a zinc compound.
[0067] The material of the metal particles surface-treated with the zinc compound can be Ag, Cu, In, Al, or alloys thereof. From the viewpoint of high electrical conductivity, the material of the metal particles is preferably Ag and / or Cu, and more preferably Ag.
[0068] The conductive paste of the present embodiment preferably contains 50% by weight or more of silver (Ag) in the metal particles, more preferably 80% by weight or more of silver (Ag), further preferably 90% by weight or more of silver (Ag), and particularly preferably 95% by weight or more of silver (Ag). In the most preferred embodiment, the metal particles of the surface-treated metal particles contained in the conductive paste of the present embodiment are composed only of silver (Ag) particles. This is because the electrical conductivity of silver is higher than that of other metals. It should be noted that in this specification, the so-called "the metal particles of the surface-treated metal particles are composed only of silver (Ag) particles" means that metal particles other than silver (Ag) particles are not intentionally used as metal particles, and the case of containing metal particles other than silver (Ag) particles that are inevitably mixed is not excluded. The same description does not exclude the substances that are inevitably mixed.
[0069] The conductive paste of the present embodiment preferably contains 50 parts by weight or more of the surface-treated metal particles based on 100 parts by weight of the conductive paste, more preferably 70 parts by weight or more, and even more preferably 80 parts by weight or more.
[0070] The conductive paste of the present embodiment preferably contains 50 to 99 parts by weight of surface-treated metal particles, more preferably 70 to 97 parts by weight, and even more preferably 80 to 95 parts by weight, relative to 100 parts by weight of the conductive paste. By setting the content within the above range, an electrode having high sulfidation resistance and low cost can be formed.
[0071] The method for producing the metal particles is not particularly limited, and the metal particles may be produced by, for example, reduction, pulverization, electrolysis, atomization, heat treatment, or a combination thereof. The flaky metal particles may be produced by, for example, flattening spherical or granular metal particles using a ball mill or the like.
[0072] The surface-treated metal particles include a surface-treated layer disposed on at least a portion of the surface of the metal particles. The surface-treated layer is a thin film formed on at least a portion of the surface of the metal particles by surface-treating the metal particles with a surface-treating agent containing a zinc compound.
[0073] As the zinc compound used as a raw material for surface treatment of metal particles, at least one selected from zinc oxide, zinc chloride, zinc sulfate, zinc hydroxide, and zinc fatty acid complexes (eg, zinc oleate) can be used.
[0074] The surface treatment layer can be formed by surface treatment using a zinc compound using a known method. Specifically, the surface treatment layer is a layer obtained by attaching a zinc soap solvent (surface treatment agent) containing zinc or zinc ions, organic matter and solvents for dispersing them to the surface of metal particles and removing the solvent using a drying process. Thus, a surface treatment layer containing a zinc compound can be formed on the surface of the metal particles. It should be noted that although there is also a technology for coating other metal particles on the surface of metal particles by reduction treatment to form a core-shell structure, when attempting to use this technology to form a surface treatment layer, in order to precipitate metal particles as a shell on the surface of the core particles (such as silver particles), the amount of metal particles in the shell becomes more. On the other hand, since the surface treatment layer is formed in a state where the zinc compound is attached to the surface of the metal particles in the present invention, the amount of zinc used can be a small amount.
[0075] As the organic matter for dispersing zinc or zinc ions, at least one selected from fatty acids and triazole compounds is preferred. In the case of using fatty acids, as fatty acids, at least one selected from butyric acid, valeric acid, caproic acid, heptanoic acid, caprylic acid, nonanoic acid, capric acid, lauric acid, myristic acid, pentadecanoic acid, palmitic acid, palmitoleic acid, heptadecanoic acid, stearic acid, oleic acid, vaccenic acid, linoleic acid, linolenic acid, eicosanoic acid, eicosadienoic acid, eicosatrienoic acid, eicosatetraenoic acid, arachidonic acid, behenic acid, lignoceric acid, nervonic acid, cerotic acid, montanic acid and melissic acid can be used. Among these fatty acids, at least one selected from palmitic acid, stearic acid and oleic acid is preferably used. As the organic matter (fatty acid) contained in the surface treatment agent, oleic acid is more preferably used. In the case of using triazole compounds as organic matter for dispersing zinc or zinc ions, benzotriazole can be used as the triazole compound.
[0076] It should be noted that the solvent contained in the surface treatment agent for forming the surface treatment layer can be any solvent as long as it is used to disperse the zinc compound and make the zinc compound adhere well to the metal particles. Examples of the solvent include alcohols such as methanol, ethanol and isopropyl alcohol (IPA), organic acids such as ethylene acetate, aromatic hydrocarbons such as toluene and xylene, N-alkylpyrrolidones such as N-methyl-2-pyrrolidone (NMP), amides such as N,N-dimethylformamide (DMF), ketones such as methyl ethyl ketone (MEK), cyclic carbonates such as terpineol (TEL) and diethylene glycol monobutyl ether (butyl carbitol, BC), bis[2-(2-butoxyethoxy)ethyl]adipate, 2,2,4-trimethylpentane-1,3-diol monoisobutyrate (TEXANOL), and water.
[0077] The surface treatment agent containing the solvent in which the zinc compound is dispersed is attached to the surface of the metal particles, and the solvent is removed by drying, thereby forming a surface treatment layer on the surface of the metal particles. In this way, surface treated metal particles can be obtained.
[0078] In addition, the surface treatment layer of the surface-treated metal particles can be manufactured as follows. That is, first, the metal particles are dispersed in water. In the water in which the metal particles are dispersed, the above-mentioned solvent in which the zinc compound is dispersed is added as a coating agent, and after obtaining a water slurry containing metal particles coated with a coating agent containing zinc, the metal particles coated with the coating agent are precipitated by decantation. Then, the supernatant is removed, and the obtained wet metal particles coated with the coating agent are added to a polar solvent with a boiling point of 150 to 300°C together with an acrylic dispersant. Thereafter, the surface-treated metal particles can be manufactured by drying for more than 12 hours at a temperature of room temperature to 100°C, preferably at a temperature below 80°C, in a nitrogen atmosphere to remove moisture. It should be noted that if the drying temperature is too high, the surface-treated metal particles will sinter, so it is not preferred.
[0079] The surface treatment layer of the surface-treated metal particles contained in the conductive paste of the present embodiment preferably further comprises an organic matter. For example, when the surface treatment layer is formed using the above-mentioned zinc compound, the surface treatment layer will comprise an organic matter. By making the surface-treated metal particles have a surface treatment layer comprising an organic matter, even if the amount of the zinc compound is a small amount, the resulting electrode can also have high resistance to sulfidation. It should be noted that the organic matter can be a liquid organic fatty acid or a solid fatty acid. As examples of liquid fatty acids, saturated fatty acids such as butyric acid, valeric acid, caproic acid, heptanoic acid, octanoic acid and nonanoic acid and unsaturated fatty acids such as myristic acid, palmitoleic acid, ricinoleic acid, oleic acid, linoleic acid and linolenic acid can be cited. These fatty acids can be used alone or in combination of more than two. Among them, oleic acid, linoleic acid or a mixture thereof is preferably used. As examples of solid fatty acids, saturated fatty acids such as capric acid, palmitic acid and stearic acid with more than 10 carbon atoms and unsaturated fatty acids such as crotonic acid and sorbic acid can be cited.
[0080] The surface treatment layer of the surface-treated metal particles used in the present embodiment is a film of a zinc compound. The present embodiment is characterized in that the surface treatment layer of the surface-treated metal particles is not a film composed of zinc metal or a zinc alloy. In the case where the surface treatment layer is a film composed of zinc metal or a zinc alloy, due to the excessive amount of zinc, there is a case where adverse effects such as an increase in the resistance of the resulting electrode are generated. In addition, after sintering, due to the presence of a large amount of zinc metal or zinc alloy on the surface of the metal particles, the possibility of hindering the brazing of metal particles such as silver particles becomes higher.
[0081] The surface treatment layer is a thin film formed on at least a portion of the surface of the metal particle. The surface treatment layer is preferably a thin film covering more than 50% of the surface of the metal particle, more preferably a thin film covering more than 80% of the surface of the metal particle, further preferably a thin film covering more than 90% of the surface of the metal particle, and particularly preferably a thin film covering more than 95% of the surface of the metal particle. The surface treatment layer is most preferably a thin film covering the entire surface of the metal particle.
[0082] The film thickness of the surface treatment layer of the surface-treated metal particles does not necessarily need to be uniform, but in order to more effectively suppress the sulfidation of the metal particles, it is preferably uniform. It should be noted that the control of the film thickness of the surface treatment layer can be controlled, for example, by adjusting the viscosity of the zinc soap solvent (surface treatment agent) in which the zinc compound is dispersed in the solvent and the concentration of the zinc compound in the zinc soap solvent (surface treatment agent). In addition, by controlling the film thickness of the surface treatment layer, the amount of zinc in the surface treatment layer can be controlled. It should be noted that the film thickness of the surface treatment layer is preferably less than 1 to 100 nm, more preferably less than 1 to 70 nm, and particularly preferably less than 1 to 50 nm. The thickness of the surface treatment layer can be measured, for example, by X-ray photoelectron spectroscopy. By setting the film thickness of the surface treatment layer to this range, an electrode with high sulfidation resistance can be formed while reducing the amount of zinc compound.
[0083] By including surface-treated metal particles that have been surface-treated with a zinc compound as (A) conductive particles in the conductive paste of this embodiment, an electrode having high sulfidation resistance can be formed without using expensive palladium. Therefore, by using the conductive paste of this embodiment, an electrode having high sulfidation resistance and low cost can be formed. In particular, when silver particles are used as metal particles, silver is easily sulfided. By using the conductive paste of this embodiment, disconnection of an electrode using silver as a main material due to sulfidation can be effectively suppressed at low cost.
[0084] For example, when silver particles are used as metal particles, the reason why the sulfidation of silver particles can be suppressed by using surface-treated metal particles (surface-treated silver particles) that have been surface-treated with a zinc compound can be inferred as follows. That is, zinc is easier to sulfidate than silver. Therefore, in an electrode made of surface-treated metal particles in which zinc exists around the metal particles (silver particles), the sulfur component in the atmosphere is absorbed by the sulfidation of zinc, and the sulfur component can be prevented from reaching the metal particles (silver particles). Therefore, it is believed that the sulfidation of silver particles (metal particles) that have the function of conductivity as an electrode can be suppressed. The same inference can be made for other metal particles other than silver particles. However, the present invention is not limited to this inference.
[0085] By making the conductive particles (A) of the conductive paste of the present embodiment contain given surface-treated metal particles, as an additional effect, the migration resistance of the obtained electrode can also be improved. The reason why the migration resistance can be improved by using surface-treated metal particles (surface-treated silver particles) that have been surface-treated with a zinc compound can be inferred as follows. Since zinc has a higher ionization tendency than silver, it is inferred that by using zinc, zinc captures electrons and can inhibit the ionization of silver. In addition, by using surface-treated metal particles that have been surface-treated with a zinc compound, the density of the electrode is improved. It is inferred that moisture is not easy to enter, thereby improving the migration resistance. However, the present invention is not limited to this inference.
[0086] In the conductive paste of the present embodiment, the content of zinc contained in the surface-treated metal particles is preferably 10 to 1000 ppm, more preferably 15 to 950 ppm, further preferably 20 to 900 ppm, and particularly preferably 22 to 850 ppm. By making the content of zinc contained in the surface-treated metal particles within the above range, the change in the resistance value of the electrode caused by the sulfidation of the electrode can be reduced. It should be noted that the content of zinc contained in the surface-treated metal particles can be measured by ICP emission spectrometry (high-frequency inductively coupled plasma emission spectrometry).
[0087] The shape of the (A) conductive particles is not particularly limited, and for example, spherical, granular, flaky, and / or scaly surface-treated metal particles can be used.
[0088] The average particle size of the (A) conductive particles is preferably 0.5 μm to 10 μm, more preferably 0.8 μm to 8 μm, and further preferably 1 μm to 7 μm. The average particle size referred to here means the volume-based median diameter (D50) obtained by the laser diffraction scattering particle size distribution measurement method. When the average particle size (D50) of the (A) conductive particles is greater than 10 μm, the sintering property is poor and a dense film cannot be obtained. In addition, when the average particle size (D50) of the (A) conductive particles is less than 0.5 μm, there is a tendency for the dispersibility to deteriorate, and it is difficult to obtain a uniform film when printing the conductive paste.
[0089] <(B)Binder resin>
[0090] The conductive paste of the present embodiment contains (B) a binder resin.
[0091] The (B) binder resin is a substance that connects the (A) conductive particles in the conductive paste. It should be noted that the conductive paste of this embodiment may contain the (C) glass powder described later, or may not contain it. The function of the (B) binder resin contained in the conductive paste of this embodiment is different when the (C) glass powder is contained and when the (C) glass powder is not contained.
[0092] When the conductive paste of the present embodiment includes the glass powder (C), the conductive paste of the present embodiment is applied to a given substrate in a manner to form a given electrode pattern, and fired at a relatively high temperature (e.g., 500 to 900° C.), thereby forming an electrode. In this case, the binder resin (B) is burned out during firing. Therefore, the function of the binder resin (B) in this case is to connect the conductive particles (A) when the conductive paste of the present embodiment is applied to a given substrate in a manner to form a given electrode pattern.
[0093] In the case where the conductive paste of the present embodiment does not contain the (C) glass powder, the conductive paste of the present embodiment is applied to a given substrate in a manner to form a given electrode pattern, and heat-treated at a relatively low temperature (e.g., 100 to 200° C.), thereby forming an electrode. In this case, the (B) binder resin will not burn out during the heat treatment. The function of the (B) binder resin in this case is not only to connect the (A) conductive particles when the conductive paste of the present embodiment is applied to a given substrate in a manner to form a given electrode pattern, but also to connect the (A) conductive particles after the heat treatment, thereby maintaining the shape of the electrode after the heat treatment.
[0094] As the (B) binder resin, for example, cellulose resins such as ethyl cellulose resin and nitrocellulose resin, acrylic resins, alkyd resins, saturated polyester resins, butyral resins, polyvinyl alcohol, and thermoplastic resins such as hydroxypropyl cellulose can be used. These resins can be used alone or in combination of two or more.
[0095] As the (B) binder resin, it is preferable to use at least one selected from cellulose-based resins such as ethyl cellulose resin and nitrocellulose resin, and alkyd resins.
[0096] In the case where the conductive paste of the present embodiment does not contain (C) glass powder, in order to improve the adhesion between the surface-treated metal particles, the conductive paste of the present embodiment may contain an epoxy resin as (B) binder resin. There is no particular limitation on the type of epoxy resin, and known epoxy resins can be used. As epoxy resins, for example, epoxy resins such as bisphenol A type, bisphenol F type, biphenyl type, tetramethylbiphenyl type, cresol novolac type, phenol novolac type, bisphenol A novolac type, dicyclopentadiene phenol condensation type, phenol aralkyl condensation type and glycidylamine type, brominated epoxy resins, alicyclic epoxy resins and aliphatic epoxy resins can be cited. These epoxy resins can be used alone or in combination of two or more. In addition, thermosetting resins other than epoxy resins can also be used for the purpose of improving the adhesion between the surface-treated metal particles. In addition, thermoplastic resins such as polyurethane resins and / or polycarbonate resins can also be used.
[0097] The content of the (B) binder resin is preferably 0.5 to 30 parts by weight, more preferably 1 to 20 parts by weight, further preferably 2 to 10 parts by weight, and particularly preferably 3 to 7 parts by weight relative to 100 parts by weight of the (A) conductive particles. When the content of the (B) binder resin in the conductive paste is within the above range, the coating property of the conductive paste to the substrate (base material) and / or the leveling property of the paste are improved, and an excellent printed shape can be obtained. On the other hand, if the content of the (B) binder resin is greater than the above range, the amount of the (B) binder resin contained in the applied conductive paste is too much. Therefore, it may not be possible to form electrodes, etc. with high precision.
[0098] <(C)Glass powder>
[0099] The conductive paste of this embodiment may further contain (C) glass frit.
[0100] When the conductive paste of the present embodiment includes the glass powder (C), the conductive paste of the present embodiment is applied to a given substrate in a manner to form a given electrode pattern, and fired at a relatively high temperature (e.g., 500 to 900° C.), thereby forming an electrode. In this case, the binder resin (B) described above is burned out during firing. By connecting the conductive particles (A) with each other using the glass powder (C) contained in the conductive paste, the shape of the electrode after firing can be maintained.
[0101] The glass frit is not particularly limited, but preferably has a softening point of 300° C. or higher, more preferably 400 to 900° C., and even more preferably 500 to 800° C. The softening point of the glass frit can be measured using a thermogravimetric measuring apparatus (eg, TG-DTA2000SA manufactured by BRUKER AXS).
[0102] Examples of (C) glass powder include borosilicate and barium borosilicate glass powders. In addition, examples of glass powder include bismuth borosilicate, alkali metal borosilicate, alkaline earth metal borosilicate, zinc borosilicate, lead borosilicate, lead borate, lead silicate, bismuth borate, and zinc borate glass powders. Two or more of these glass powders may be mixed and used. From the perspective of environmental considerations, the glass powder is preferably lead-free.
[0103] The glass frit preferably contains at least one selected from ZnO, Bi2O3, BaO, Na2O, CaO, and Al2O3. The glass frit more preferably contains at least one selected from ZnO and Bi2O3.
[0104] When the conductive paste of the present embodiment contains (C) glass frit, the glass frit further preferably contains ZnO. When glass frit containing ZnO (zinc-based glass frit) is used as the glass frit, an electrode with higher sulfidation resistance can be obtained.
[0105] When the conductive paste of the present embodiment contains (C) glass frit, the glass frit further preferably contains Bi 2 O 3. When glass frit (bismuth-based glass frit) containing Bi 2 O 3 is used as the glass frit, the density of the electrode can be improved.
[0106] The average particle size of the glass powder is preferably 0.1 to 20 μm, more preferably 0.2 to 10 μm, and most preferably 0.5 to 5 μm. The average particle size here refers to the volume-based median diameter (D50) obtained by laser diffraction scattering particle size distribution measurement.
[0107] When the conductive paste of the present embodiment contains (C) glass powder, the content of (C) glass powder is preferably 0.05 to 10 parts by weight, more preferably 0.07 to 8 parts by weight, and further preferably 0.08 to 6 parts by weight relative to 100 parts by weight of (A) conductive particles. When the content of the glass powder is less than this range, the adhesion between the electrode obtained by firing the conductive paste and the substrate (base material) is reduced. When the content of the glass powder is greater than this range, the resistance value of the electrode obtained by firing the conductive paste is high, and the surface of the fired body is covered with a glass component, so the plating property deteriorates. It should be noted that when the content of the glass powder is small, a low-resistance electrode can be obtained. In addition, when the content of the glass powder is large, an electrode with excellent chemical resistance can be obtained. Chemical resistance is a characteristic required because a plating pretreatment is required when a plating film is formed on the surface of the electrode. The plating pretreatment is performed for the purpose of removing contaminants from the surface of the electrode, activating the surface of the electrode, and making it a clean state suitable for plating. The pollutants that should be removed can be roughly divided into organic and inorganic types. The pretreatment process is not a process that uses a single process to remove all pollutants. For example, organic substances are removed by using a process using an alkaline detergent. Inorganic substances are removed by using a process using an acidic detergent. Therefore, the electrode is required to have high chemical resistance.
[0108] When the conductive paste of the present embodiment includes (C) glass powder, the glass powder softens as the temperature rises, and the sintering (firing) of the (A) conductive particles is advanced. When the glass powder content is high, the glass component may be squeezed out to the surface of the fired body. In this case, the surface of the fired body may be covered with the glass component. When the (C) glass powder includes zinc oxide, the Zn component in the glass powder precipitates as ZnO at the crystallization temperature, and thus can contribute to the sulfurization resistance of the (A) conductive particles after firing, similarly to the zinc in the surface-treated metal particles.
[0109] <(D)Dispersant>
[0110] The conductive paste of the present embodiment may contain (D) a dispersant. When the conductive paste of the present embodiment contains the (D) dispersant, the dispersibility of the (A) conductive particles in the conductive paste can be improved, and aggregation of the (A) conductive particles can be prevented.
[0111] As the (D) dispersant, a known dispersant can be used. As the (D) dispersant, for example, an acid-type dispersant can be used.
[0112] <(E)Solvent>
[0113] The conductive paste of the present embodiment may contain (E) a solvent. Examples of the solvent include alcohols such as methanol, ethanol, and isopropyl alcohol (IPA), organic acids such as ethylene acetate, aromatic hydrocarbons such as toluene and xylene, N-alkylpyrrolidones such as N-methyl-2-pyrrolidone (NMP), amides such as N,N-dimethylformamide (DMF), ketones such as methyl ethyl ketone (MEK), cyclic carbonates such as terpineol (TEL) and diethylene glycol monobutyl ether (butyl carbitol, BC), bis[2-(2-butoxyethoxy)ethyl]adipate, 2,2,4-trimethylpentane-1,3-diol monoisobutyrate (TEXANOL), and water.
[0114] The content of the solvent in the conductive paste of the present embodiment is not particularly limited. For example, the content of the solvent is preferably 1 to 100 parts by weight, more preferably 5 to 60 parts by weight, and even more preferably 8 to 35 parts by weight, based on 100 parts by weight of the (A) conductive particles.
[0115] The viscosity of the conductive paste of the present embodiment is preferably 50 to 700 Pa·s (shear rate: 4.0 sec. -1 ), more preferably 100 to 300 Pa·s (shear rate: 4.0 sec -1 ). The viscosity of the conductive paste of the present embodiment can be adjusted by appropriately controlling the content of the solvent. By adjusting the viscosity of the conductive paste to this range, the coating property and / or operability of the conductive paste on the substrate (base material) become good, and the conductive paste can be applied to the substrate with a uniform thickness. It should be noted that the viscosity of the conductive paste can be measured using an HB type viscometer (manufactured by Brookfield) (SC4-14 rotor) at a temperature of 25°C and 10 rpm.
[0116] <(F)Curing agent>
[0117] The conductive paste of the present embodiment preferably further includes (F) a curing agent. When the conductive paste of the present embodiment includes an epoxy resin as the (B) binder resin, the curing of the epoxy resin can be appropriately controlled by including the (F) curing agent.
[0118] (F) A known curing agent can be used. As the (F) curing agent, it is preferred to include at least one selected from a phenolic curing agent, a cationic polymerization initiator, an imidazole curing agent, and a boron trifluoride compound. As the boron trifluoride compound, boron trifluoride monoethylamine, boron trifluoride piperidine, and boron trifluoride diethyl ether can be cited. As the (F) curing agent, boron trifluoride monoethylamine can be preferably used.
[0119] In the conductive paste of the present embodiment, when the total weight of the conductive particles (A) and the epoxy resin as the binder resin (C) is 100 parts by weight, the conductive paste preferably contains 0.1 to 5 parts by weight of the curing agent (F), more preferably 0.15 to 2 parts by weight, further preferably 0.2 to 1 part by weight, and particularly preferably 0.3 to 0.6 parts by weight. By setting the weight ratio of the curing agent (F) to a given range, the epoxy resin as the binder resin component (B) can be properly cured, and an electrode of a desired shape can be obtained.
[0120] <Other ingredients>
[0121] The conductive paste of the present embodiment may contain other additives, such as organic additives and inorganic additives, etc. Specifically, as additives, a silica filler, a rheology modifier, and / or a pigment may be contained.
[0122] By adding an organic additive as an additive to the conductive paste, the printability of the conductive paste can be improved. By adding a dispersant as an additive to the conductive paste, the dispersibility of conductive particles can be improved. By adding an inorganic additive as an additive to the conductive paste, the adhesion of the conductive paste after firing can be improved.
[0123] The conductive paste of the present embodiment can be produced by mixing the above-mentioned components using, for example, a pestle, a pot mill, a three-roll mill, a rotary mixer, and / or a twin-screw mixer.
[0124] <Electrode>
[0125] The present embodiment is an electrode obtained by firing or heat-treating the conductive paste of the present embodiment described above.
[0126] When the conductive paste of the present embodiment includes (C) glass powder, the conductive paste of the present embodiment is applied to a given substrate in a manner to form a given electrode pattern, and fired in an air atmosphere at a relatively high temperature (e.g., 500 to 900° C.), thereby forming an electrode. Therefore, the electrode when the conductive paste of the present embodiment includes (C) glass powder can contain (A') conductive particles containing surface-treated metal particles and (C') glass components made of (C) glass powder. After firing, the (A') conductive particles become a sintered state. It should be noted that when the conductive paste of the present embodiment is fired at a relatively high temperature (e.g., 500 to 900° C.), the (B) binder resin and (E) solvent contained in the conductive paste are vaporized or burned during firing. Therefore, the electrode does not substantially contain the (B) binder resin and (E) solvent.
[0127] When the conductive paste of the present embodiment does not contain the (C) glass powder, the conductive paste of the present embodiment is applied to a given substrate in a manner to form a given electrode pattern, and heat-treated at a relatively low temperature (e.g., 100 to 200° C.), thereby forming an electrode. Therefore, the electrode of the present embodiment when the conductive paste of the present embodiment does not contain the (C) glass powder can contain the (A') conductive particles containing surface-treated metal particles and the (B') binder component made of the (B) binder resin. The (A') conductive particles are connected via the (B') binder component.
[0128] Since the surface-treated metal particles contained in the conductive paste of the present embodiment are surface-treated with a zinc compound, the electrode of the present embodiment contains zinc. The electrode of the present embodiment preferably contains 0.1 to 10% by weight of zinc, more preferably 0.5 to 8% by weight of zinc, and further preferably 1 to 5% by weight of zinc. It should be noted that, in the case where the conductive paste of the present embodiment contains (C) glass powder, the electrode of the present embodiment may contain zinc derived from the (C) glass powder. By making the electrode of the present embodiment contain a given amount of zinc, the electrode of the present embodiment can have high resistance to sulfidation. It should be noted that the zinc content in the electrode can be measured by elemental analysis based on EDS (Energy Dispersive X-ray Spectroscopy).
[0129] The sheet resistance of the thin film used as the electrode of this embodiment varies depending on the film thickness, but can be generally set to about 10 mΩ / □ (10 mΩ / square) or less. Therefore, it can be preferably used to form an electrode requiring low resistance.
[0130] Next, a method for forming an electrode on a substrate (base material) using the conductive paste of the present embodiment is described. First, the conductive paste is applied to the substrate. The conductive paste can be applied by any method, for example, by glue dripping, glue jetting, stencil printing, screen printing, pin transfer, or stamping.
[0131] In the case where the conductive paste of the present embodiment includes (C) glass powder, after the conductive paste is applied to the substrate, it is dried as needed, and the substrate is placed in a firing furnace or the like. Thereafter, the conductive paste applied to the substrate is fired at 500 to 900°C, more preferably at 600 to 880°C, and further preferably at 700 to 870°C. A specific example of the firing temperature is 850°C. As a result, the solvent component contained in the conductive paste evaporates below 300°C, and the resin component is burned at 400°C to 600°C to form a fired body (electrode) of the conductive paste. It is also believed that the organic component contained in the surface-treated metal particles disappears due to firing in an air atmosphere, and the zinc in the zinc compound exists as a coating on the surface of the metal particles in the form of zinc oxide. The electrode obtained in this way has high sulfidation resistance and excellent adhesion to the substrate.
[0132] In the case where the conductive paste of the present embodiment does not contain (C) glass powder, after the conductive paste is applied to the substrate, the substrate is placed in a heat treatment furnace or the like. Thereafter, the conductive paste applied to the substrate is heat treated at 100 to 200°C, more preferably at 150 to 200°C. The heat treatment time is preferably 20 to 90 minutes, more preferably 30 to 60 minutes. A specific example of the heat treatment conditions is 150°C and 60 minutes. Thus, the solvent component contained in the conductive paste is dried, and the conductive paste is thermally cured, thereby forming a cured body (electrode) of the conductive paste. The electrode obtained in this way has high resistance to sulfidation and excellent adhesion to the substrate.
[0133] In addition, the electrode obtained as described above using the conductive paste of this embodiment can have an additional advantage of improved migration resistance. This additional advantage can be obtained both when the conductive paste contains (C) glass powder and when it does not contain (C) glass powder. However, it is considered that this advantage is not necessarily an essential effect of the conductive paste of this embodiment, but is an advantage.
[0134] <Electronic components or electronic equipment>
[0135] The present embodiment is an electronic component or electronic device having the above-mentioned electrode. In this specification, the so-called electronic component means a component used in electronic devices such as chip resistors and substrate circuits. In this specification, the so-called electronic component means a component that works electronically, specifically, it can be a component that operates below 48V of direct current. In this specification, the so-called electronic device means a device including an electronic component having an electrode of this embodiment.
[0136] The conductive paste of the present embodiment can be used for forming circuits of electronic components or electronic devices, forming electrodes, and bonding electronic components to a substrate (base material) of a device (eg, semiconductor chip).
[0137] The conductive paste of this embodiment can be preferably used for forming electrodes of a chip resistor. Figure 1 An example of the cross-sectional structure of the chip resistor 100 of the present embodiment is shown in FIG. The chip resistor 100 may have a rectangular alumina substrate 102 and a resistor 104 and a lead electrode 106 arranged on the surface of the alumina substrate 102. The lead electrode 106 is an electrode for extracting electricity from the resistor 104. In addition, a lower surface electrode 108 for mounting the chip resistor 100 on the substrate may be arranged on the lower surface of the alumina substrate 102. In addition, a connecting electrode 110 for connecting the lead electrode 106 and the lower surface electrode 108 may be arranged on the end surface of the alumina substrate 102. Using the conductive paste of the present embodiment, at least one of the lead electrode 106, the lower surface electrode 108 and the connecting electrode 110 may be formed. It is particularly preferred to form the lead electrode 106 using the conductive paste of the present embodiment. It should be noted that a nickel plated film 112 and a tin plated film 114 may be disposed on the upper surfaces (surfaces on the opposite side to the alumina substrate 102 ) of the extraction electrode 106 , the lower surface electrode 108 , and the connection electrode 110 .
[0138] The electrodes of this embodiment are not limited to the electrodes of chip resistors. The electrodes formed using the conductive paste of this embodiment can be used as electrodes of various electronic components. As electronic components, passive components (such as chip resistors, capacitors, resistors and inductors, etc.), circuit substrates (for example, circuit substrates on which a given circuit (electrode or wiring) is formed on a substrate such as an aluminum oxide substrate, an aluminum nitride substrate and a glass substrate), solar cell units and electromagnetic wave shielding, etc. can be cited. The conductive paste of this embodiment can be used to form the electrodes and / or wiring of these electronic components. As electronic devices including electronic components having electrodes of this embodiment, electronic devices including semiconductor devices, solar power generation modules and circuit substrates can be cited.
[0139] The conductive paste of this embodiment can be used as a chip pasting material for mounting a semiconductor chip in a semiconductor device. In the case where the semiconductor device is a power semiconductor device, it can be used as a solder for mounting a power semiconductor chip. The conductive paste of this embodiment can be used as an electrode of a solar cell. The conductive paste of this embodiment can be used as a conductive adhesive. In addition, the conductive paste of this embodiment is not limited to the formation of terminal electrodes of chip resistors, and can also be suitably used as a conductive paste for terminal electrodes of passive components such as MLCC and chip inductors.
[0140] By using the conductive paste of this embodiment, it is possible to form an electrode having high sulfurization resistance, low resistance, and low cost. Therefore, by using the conductive paste of this embodiment, it is possible to obtain electronic components such as chip resistors having electrodes with high reliability at low cost.
[0141] Example
[0142] Hereinafter, the present invention will be specifically described using Examples, but the present invention is not limited to these Examples.
[0143] [Preparation of conductive paste]
[0144] The following (A) to (F) components were mixed in the proportions shown in Tables 1 to 4 to prepare a conductive paste. It should be noted that the proportions of the components shown in Tables 1 to 4 are all expressed in parts by weight. In Tables 1 to 4, the weight of the conductive particles (A) (the total weight of the metal particles and the surface-treated metal particles) is set to 100 parts by weight. In addition, the average particle size refers to the volume-based median diameter (D50) obtained by laser diffraction scattering particle size distribution measurement method.
[0145] (A) Conductive particles
[0146] Table 5 shows metal particles a1 to a3 and surface-treated metal particles A1 to A8 used as (A) conductive particles ((A) component) of examples and comparative examples. Metal particles a1 and a2 are silver particles, and metal particle a3 is a zinc particle. Metal particles a1 to a3 are not surface-treated. Regarding surface-treated metal particles A1 to A8, a zinc soap solvent (surface treatment agent) obtained by dispersing a zinc compound in a solvent is attached to the surface of the metal particles as silver particles, and the solvent is removed by a drying process, thereby performing surface treatment. Therefore, the surface-treated metal particles A1 to A8 have a surface-treated layer containing a zinc compound. In the "Zinc Content" column of Table 5, the weight ratio of zinc contained in the surface-treated layer relative to the weight of the surface-treated metal particles A1 to A8 is shown in units of weight ppm. The weight ratio of zinc in the surface-treated metal particles is measured by ICP emission spectrometry (high-frequency inductively coupled plasma emission spectrometry). The surface-treated layer is formed on the surface-treated metal particles A1 to A8 as described above.
[0147] The surface treatment of the zinc compound on the silver particles is performed as follows. That is, the surface treatment of the zinc compound on the silver particles is performed using a zinc soap solvent (surface treatment agent) containing a zinc compound, an organic substance for dispersing the zinc compound, and a solvent. The zinc soap solvent (surface treatment agent) is attached to the surface of the silver particles, and the solvent is removed by a drying process, thereby performing the surface treatment. Zinc oleate is used as the zinc compound. In addition, oleic acid is used as a dispersant contained in the surface treatment agent for the silver particles.
[0148] (B) Binder resin
[0149] (B) Binder resins (resins B1 to B6) used in Examples and Comparative Examples are shown in Table 6. Tables 1 to 4 show the blending amounts of resins B1 to B6 in the conductive pastes of Examples and Comparative Examples.
[0150] (C) Glass powder
[0151] The (C) glass frits (GF-C1 and GF-C2) used in Examples and Comparative Examples are shown in Table 7. Tables 1 to 4 show the blending amounts of the glass frits GF-C1 and GF-C2 in the conductive pastes of Examples and Comparative Examples.
[0152] (D) Dispersant
[0153] In the conductive pastes of Examples and Comparative Examples, an acidic low molecular weight dispersant ESLEAM 221P (manufactured by NOF Corporation) was used as the dispersant (D) (dispersant D). Tables 1 to 4 show the blending amounts of the dispersant D in the conductive pastes of Examples and Comparative Examples.
[0154] (E) Solvent
[0155] The (E) solvents (solvents E1 to E4) used in Examples and Comparative Examples are shown in Table 8. Tables 1 to 4 show the blending amounts of the solvents E1 to E4 in the conductive pastes of Examples and Comparative Examples.
[0156] (F) Curing agent
[0157] In the conductive pastes of Examples 20 to 22, boron trifluoride monoethylamine (Stellachemifa Co., Ltd.) was used as (F) curing agent F. Table 4 shows the blending amounts of the curing agent F in the conductive pastes of Examples 20 to 22.
[0158] [Preparation of Test Specimen 50 for Sulfurization Resistance Test]
[0159] Figure 2 A schematic diagram of a test piece 50 for the anti-sulfurization test is shown in . Using a conductive paste containing (C) glass frit, test pieces 50 for the anti-sulfurization test of Examples 1 to 19 and Comparative Examples 1 to 3 were prepared by the following procedure.
[0160] First, on an alumina substrate 52 (purity 96%) for sulfurization resistance test of 20 mm×20 mm×1 mm (t), a screen printing was performed to form a Figure 2The conductive paste was applied in the manner of a zigzag sulfide resistance test print pattern 54 shown. The length between the two ends 54a and 54b of the sulfide resistance test print pattern 54 was 71 mm, and the width of the sulfide resistance test print pattern 54 was 1 mm. In order to form the sulfide resistance test print pattern 54 of the conductive paste, a 325-mesh stainless steel screen (emulsion thickness 5 μm) was used for screen printing. Then, the sulfide resistance test print pattern 54 of the conductive paste was dried at 150°C for 10 minutes using an intermittent hot air dryer. After the sulfide resistance test print pattern 54 of the conductive paste was dried, the sulfide resistance test print pattern 54 was fired using a belt-type firing furnace. The firing temperature was maintained at 850°C for 10 minutes. The total time from entering the firing furnace to taking it out was 60 minutes. The test pieces 50 of Examples 1 to 19 and Comparative Examples 1 to 3 were prepared as described above.
[0161] In Examples 20 to 22 using the conductive paste not containing the (C) glass powder, the conductive pastes of Examples 20 to 22 were used in the same manner as in Examples 1 to 19 and Comparative Examples 1 to 3, and a zigzag sulfidation resistance test printed pattern 54 having a width of 1 mm and a length of 71 mm was formed by screen printing on an alumina substrate 52 for sulfidation resistance test (purity 96%) of 20 mm×20 mm×1 mm (t) (see Figure 2 ). Then, the printed pattern 54 for the sulfurization resistance test of the conductive paste was heat-treated at 150° C. for 10 minutes using an intermittent hot air dryer, thereby curing the printed pattern 54 for the sulfurization resistance test. The test pieces 50 of Examples 20 to 22 were prepared as described above.
[0162] [Sulfurization resistance test method]
[0163] First, the resistance (initial resistance) between the two ends 54a and 54b of the printed pattern 54 for the sulfur resistance test of the test piece of the embodiment and the comparative example is measured. Then, a dish (height 18mm, diameter 86mm) with 10g of sulfur powder added in a flat manner is placed at the bottom of a glass desiccator (height 420mm, diameter 300mm), and the test piece of the embodiment and the comparative example is placed on the shelf. The desiccator is kept in a constant temperature bath at 60°C for 150 hours to vulcanize the test piece. Then, the resistance after vulcanization is measured. In the "Resistance Value Change Ratio (Sulfur Resistance Test)" column of Tables 1 to 4, the resistance value change ratio of the resistance after vulcanization relative to the initial resistance of the embodiment and the comparative example is expressed in percentage units. The resistance value change ratio can be expressed by the following formula.
[0164] Resistance change ratio = (resistance after vulcanization - initial resistance) / initial resistance
[0165] [Preparation of test pieces for adhesive strength test]
[0166] Using the prepared conductive paste, test pieces of Examples 1 to 19 and Comparative Examples 1 to 3 containing (C) glass powder were prepared using the following steps. First, the conductive paste was applied to an alumina substrate (purity 96%) of 20 mm × 20 mm × 1 mm (t) by screen printing. Thus, 25 (5 × 5) bonding strength test patterns consisting of square pads with a side length of 1.5 mm were formed on the alumina substrate. In order to form the bonding strength test pattern of the conductive paste, screen printing was performed using a 325-mesh stainless steel screen (emulsion thickness 5 μm).
[0167] Then, the conductive paste was dried at 150°C for 10 minutes using an intermittent hot air dryer. After the conductive paste bonding strength test pattern was dried, the conductive paste bonding strength test pattern was fired using a belt-type firing furnace. The firing temperature was maintained at 850°C for 10 minutes. The total time from entering the firing furnace to taking it out was 60 minutes. Test pieces of Examples 1 to 19 and Comparative Examples 1 to 3 were prepared as described above.
[0168] Then, the bonding strength test pattern was plated with Ni / Au. Then, after the solder (M705 manufactured by Senju Metal Industry Co., Ltd., a Sn alloy containing 3.0 wt% Sn-Ag and 0.5 wt% Cu) was attached to the bonding strength test pattern at 260°C for 3 seconds, the Sn-plated soft copper wire (diameter 0.8 mm) was brazed to the bonding strength test pattern. It should be noted that among the 5×5 bonding strength test patterns on the alumina substrate, 5 Sn-plated soft copper wires were brazed one each in the 2nd column, totaling 5 Sn-plated soft copper wires, and 5 Sn-plated soft copper wires were brazed one each in the 4th column, totaling 5 Sn-plated soft copper wires, thereby brazing the Sn-plated soft copper wires. A total of 10 Sn-plated soft copper wires were brazed, and the tensile bonding strength of the lead was measured using a strength tester. Specifically, the alumina substrate was placed vertically at an angle of 90 degrees relative to the strength tester so that the pattern for the adhesive strength test was on the upper surface, and the lead was pulled vertically upward relative to the alumina substrate to measure the tensile adhesive strength. The force (N) when the lead was peeled off was defined as the tensile adhesive strength.
[0169] As with the test pieces of Examples 1 to 19 and Comparative Examples 1 to 3, the conductive paste prepared as Examples 20 to 22 was applied by screen printing on an alumina substrate (purity 96%) of 20 mm × 20 mm × 1 mm (t). Thus, 25 (5 × 5) bonding strength test patterns consisting of square pad shapes with a side length of 1.5 mm were formed on the alumina substrate. Then, the conductive paste was heat-treated at 150°C for 10 minutes using a hot air dryer, thereby curing the bonding strength test pattern of the conductive paste. Test pieces of Examples 20 to 22 were prepared as described above. Then, as with Examples 1 to 19 and Comparative Examples 1 to 3, the bonding strength test patterns of Examples 20 to 22 were plated with Ni / Au. Then, similarly to the test pieces of Examples 1 to 19 and Comparative Examples 1 to 3, Sn-plated soft copper wires (leads) were soldered to the bonding strength test patterns, and the tensile bonding strength of the leads was measured using a strength tester.
[0170] The results of the adhesive strength test were obtained by measuring the tensile adhesive strength of 10 test pieces of each example and each comparative example. The "Adhesive Strength (N)" column in Tables 1 to 4 shows the average value of the tensile adhesive strength of the 10 test pieces of each example and each comparative example measured as described above.
[0171] [Migration resistance test]
[0172] Figure 3 2 shows an optical microscope photograph of test printed patterns 64a and 64b of an example of a test piece 60 for the migration resistance test. Using the prepared conductive paste, test pieces 60 for the migration resistance test of Examples 3, 4, 20 to 22, and Comparative Example 1 were prepared by the following procedure.
[0173] The test pieces 60 for the migration resistance test of Examples 3 and 4 and Comparative Example 1 were prepared by the following steps. First, on an alumina substrate 62 (purity 96%) for the migration resistance test of 110 mm×20 mm×0.8 mm (t), a screen printing method was used. Figure 3 and as Figure 3 Enlarged photo of Figure 4As shown, the conductive paste is applied in a staggered manner with two comb-shaped migration test print patterns 64a and 64b. The migration test print pattern 64a is connected to the first electrode 66a, and the migration test print pattern 64b is connected to the second electrode 66b. The printing width L of the migration test print patterns 64a and 64b is 200 μm, and the gap S between the migration test print patterns 64a and 64b is 200 μm. In order to form the migration test print patterns 64a and 64b of the conductive paste and the electrodes 66a and 66b, a 400-mesh stainless steel screen (emulsion thickness 10 μm) is used for screen printing. Then, an intermittent hot air dryer is used to dry the migration test print patterns 64a and 64b of the conductive paste and the electrodes 66a and 66b at 150°C for 10 minutes. After drying the printed patterns 64a, 64b and electrodes 66a, 66b of the conductive paste for migration resistance test, the printed patterns 64a, 64b and electrodes 66a, 66b for migration resistance test were fired using a belt-type firing furnace. The firing temperature was maintained at 850°C for 10 minutes. The total time from entering the firing furnace to taking it out was 60 minutes. The thickness of the printed patterns 64a, 64b and electrodes 66a, 66b for migration resistance test after firing was 10 to 20 μm. As described above, the test pieces 60 for migration resistance test of Examples 3 and 4 and Comparative Example 1 were prepared.
[0174] The test pieces 60 for the migration resistance test of Examples 20 to 22 were prepared by the following steps. First, as in the test pieces 60 of Examples 3 and 4 and Comparative Example 1, a 110 mm × 20 mm × 0.8 mm (t) alumina substrate 62 (purity 96%) was screen printed as follows: Figure 3 and Figure 4 As shown in FIG. 1 , the conductive paste was applied in a staggered manner with two comb-shaped printed patterns 64a and 64b for the migration resistance test. Then, the conductive paste was heat-treated at 200° C. for 30 minutes using a hot air dryer to cure the pattern for the adhesive strength test of the conductive paste. As described above, test pieces for the migration resistance test of Examples 20 to 22 were prepared.
[0175] The migration resistance of the migration resistance test printed patterns 64a and 64b of Examples 3, 4, 20 to 22 and Comparative Example 1 was measured by the following steps. Figure 3As shown, a voltage (40V) is applied between the first electrode 66a and the second electrode 66b of the two printed patterns 64a and 64b for the migration resistance test. The insulation resistance value between the first electrode 66a and the second electrode 66b is measured in a state of being stored in an environment of a temperature of 85°C and a humidity of 85%. The insulation resistance value is calculated based on the measured value of the current flowing between the first electrode 66a and the second electrode 66b and the applied voltage of 40V. The test piece 60 to which the applied voltage of 40V is applied is maintained in an environment of a temperature of 85°C and a humidity of 85% for a maximum of 500 hours. Table 9 shows the results of the migration resistance test. The insulation resistance value of all samples before the test was 10 7 Ω or more. The insulation resistance value will be reduced to 10 within 500 hours. 6 The test pieces 60 with an insulation resistance value of less than 10Ω were judged as defective and recorded as "defective" in Table 9. 6 The test piece 60 with a value of Ω or less was judged to be excellent in migration resistance and was recorded as "good" in Table 9.
[0176] [Zinc content of electrode]
[0177] Using the conductive paste prepared in Example 3, the amount of zinc on the electrode surface of the test piece after the sulfidation resistance test was quantitatively analyzed by EDS (energy dispersive X-ray spectroscopy). As a result, it was confirmed that 3.09% of zinc components were precipitated on the zinc surface. In addition, Fig.13 : Shown in FIG. 3 is a SEM photograph (magnification 5000 times) for EDS analysis of the distribution of zinc on the electrode surface of the test piece after the sulfidation resistance test. Fig.14 and Fig.15 The grayscale indicates the values corresponding to the values determined by EDS analysis. Fig.13 The results are obtained by looking at the distribution of zinc oxide (ZnO) and zinc aluminate (ZnAlO) in the SEM images shown. Figures 13-15 As shown, it can be confirmed that zinc is not present in the form of zinc alone on the electrode surface, but in the form of zinc oxide and zinc aluminate.
[0178] [Surface and cross-sectional observation using SEM and cross-sectional observation using EDS analysis]
[0179] Figure 5 and Figure 6 : shows SEM photographs taken at a magnification of 5000 times of the surface and cross section of a test piece produced under the same conditions as the test piece 50 of the sulfurization resistance test of Example 3 having a smaller resistance value change ratio, using a scanning electron microscope (SEM). Figure 7 and Figure 8 4 shows the results of EDS analysis of a cross section of a test piece produced under the same conditions as the test piece 50 in the sulfurization resistance test of Example 3. Fig. 9 and Fig.10 : shows SEM photographs taken at a magnification of 5000 times of the surface and cross section of a test piece produced under the same conditions as the test piece 50 of the sulfurization resistance test of Comparative Example 1 having a large resistance value change ratio. Fig.11 and Fig.12 : shows the results of EDS analysis of a cross section of a test piece produced under the same conditions as the test piece 50 of the sulfurization resistance test of Comparative Example 1. It should be noted that, similarly to the case of the sulfurization resistance test, the test piece was stored in a sulfur atmosphere (60° C.) for 150 hours, and then SEM observation and EDS analysis were performed.
[0180] [evaluate]
[0181] As is clear from the results shown in Tables 1 to 4, the resistance value change ratio of the electrode patterns obtained by firing the conductive pastes of Examples 1 to 22 was 220.2% or less (Example 19), which is a relatively low value. In contrast, the resistance value change ratio of the electrode patterns obtained by firing the conductive pastes of Comparative Examples 1 to 3 was 300% or more (Comparative Example 1), or the resistance value after storage in the sulfur atmosphere of the sulfurization resistance test was too high to be measured.
[0182] As is clear from the results shown in Tables 1 to 4, the tensile adhesive strength of the bonding strength test patterns obtained by firing the conductive pastes of Examples 1 to 22 ranged from 17.2 N (Examples 7, 17, and 21) to 25.9 N (Example 10), and high tensile adhesive strengths were obtained. On the other hand, the tensile adhesive strengths of the electrode patterns obtained by firing the conductive pastes of Comparative Examples 1 to 3 ranged from 10.1 N (Comparative Example 3) to 20.1 N (Comparative Example 1), which was a range that did not pose a problem in terms of tensile adhesive strength.
[0183] As is apparent from the results shown in Table 9, the electrodes of Examples 3, 4, and 20 to 22 of the present embodiment are superior to Comparative Example 1 in migration resistance.
[0184] Compare Figure 5 and Figure 6 The embodiment 3 shown is Fig. 9 and Fig.10 As can be understood from the SEM photograph of Comparative Example 1 shown, compared with Example 3, Comparative Example 1 forms large crystals of silver sulfide 20 due to sulfidation. Fig.10 In the figure, it can be seen that a gap 30 is formed in a part of the electrode 10. Fig.11 and Fig.12 Comparative Example 1 and Figure 7 and Figure 8The EDS analysis results of Example 3 shown above also show that larger crystals of silver sulfide 20 are formed in Comparative Example 1 due to sulfidation than in Example 3. Therefore, it can be said that the electrode of the example of the present embodiment has higher sulfidation resistance than the comparative example.
[0185]
[0186]
[0187]
[0188]
[0189]
[0190]
[0191]
[0192]
[0193]
[0194] Description of Reference Numerals
[0195] 10 electrode, 20 silver sulfide, 30 gap, 50 test piece for sulfurization resistance test, 52 alumina substrate for sulfurization resistance test, 54 printed pattern for sulfurization resistance test, 54a, 54b end of printed pattern for sulfurization resistance test, 60 test piece for migration resistance test, 62 alumina substrate for migration resistance test, 64a, 64b printed pattern for migration resistance test, 66a first electrode, 66b second electrode, 100 chip resistor, 102 alumina substrate, 104 resistor body, 106 lead electrode, 108 lower surface electrode, 110 connection electrode, 112 nickel plating film, 114 tin plating film.
Claims
1. A conductive paste comprising (A) conductive particles and (B) a binder resin, (A) the conductive particles include surface-treated metal particles, The surface-treated metal particle includes a metal particle and a surface-treated layer disposed on at least a portion of a surface of the metal particle. The surface treatment layer includes a zinc compound.
2. The conductive paste according to claim 1, wherein The surface-treated metal particles contain zinc in an amount of 10 ppm to 1000 ppm.
3. The conductive paste according to claim 1 or 2, wherein The surface treatment layer further comprises an organic matter.
4. The conductive paste according to any one of claims 1 to 3, wherein The metal particles contain 50 wt % or more of silver.
5. The conductive paste according to any one of claims 1 to 4, wherein The average particle size D50 of the (A) conductive particles is 0.5 μm to 10 μm.
6. The conductive paste according to any one of claims 1 to 5, wherein The content of the (B) binder resin is 0.1 to 30 parts by weight based on 100 parts by weight of the (A) conductive particles.
7. The conductive paste according to any one of claims 1 to 6, wherein The conductive paste further includes (C) glass frit.
8. The conductive paste according to claim 7, wherein The (C) glass frit contains ZnO.
9. The conductive paste according to claim 7 or 8, wherein The conductive paste contains the (C) glass frit in an amount of 0.05 to 10 parts by weight based on 100 parts by weight of the (A) conductive particles. 10 . An electrode obtained by firing or heat-treating the conductive paste according to claim 1 .
11. The electrode according to claim 10, wherein The electrode contains 0.1 wt % to 10 wt % zinc. 12 . An electronic component or electronic device comprising the electrode according to claim 10 or 11 .
Citation Information
Patent Citations
Paste for forming electrode on chip resistor
JP1995335402A
Electroconductive paste, electrode and chip resistor
WO2021145269A1